The Impact of The Digital Economy on Resource Consumption - Aminova Niginabonu Bakhriddinovna; Raxmonqulova Nafisa Olimjon kizi (Genius Journals, 2021)
Digital platforms have provided great efficiency in coordinating exchange practices among many users Many of the sharing platforms have often formed what is known as the “unified economy” or more precisely the “Digital Exchange Economy” (DSE). A distinctive feature of DSE is the ability to expand access to a variety of resources within large and spatially distributed communities of consumers; a feature that does not exist in traditional, small-scale exchanges. ICT) is known for its role in changing exchange practices and helping to expand exchange networks. Such comprehensive changes resulting from digital development may raise a number of important questions about sustainability because often comes with opportunities and risks.
Keywords: investment; market rule; economy; infrastructure